Coaching track & field successfully - Guthrie, Mark. (United States : Human Kinetics, 2003)
This title provides coaches with a blueprint for building a successful track and field programme, including information on managing the team off the track, planning for big events and motivating athletes to excel.
Includes index.
Keywords: Track and field-Coaching; Track and field-Training